(untitled) (Research, Society and Development, 2025)
This study aimed to identify the occurrence of oral manifestations in patients admitted to the ICU and who died during the COVID-19 pandemic. In addition, the participation of the dental surgeon in the multi-professional team responsible for the care of these patients was analyzed. This is a retrospective study, carried out in a public health unit in the state of Bahia, whose information was obtained from electronic medical records. The descriptive analysis of the data used the mean, standard deviation (SD), median, interquartile range (IQR), maximum and minimum values and absolute and relative frequencies. The normal distribution of the quantitative variables was checked using the Shapiro-Wilk and Kolmogorov-Smirnov tests. In this study, 101 patients were analyzed, of whom 84.2% reported no oral lesions and 15.8% reported oral lesions. With the significant impacts on global health in the pandemic period, the need for integrated approaches to caring for the population was evident, always considering the relationship between oral and systemic health. It is essential to implement public policies that guarantee the inclusion of dental surgeons in Intensive Care Units.